The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7cc04346e
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanically responsive crystalline organic cantilever

Abstract: We report thermo-mechanically responsive and thermochromic behavior in the single crystalline organic semiconductor butoxyphenyl N-substituted naphthalene diimide (BNDI). We show that initially monoclinic single crystals of BNDI undergo a single-crystal to single-crystal transition to a triclinic phase. This transition accompanies large changes in the crystal packing, a visible decrease in crystal size, reversible thermochromic behavior, and motion including bending, jumping, and splitting. We have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…The difference in these transition enthalpies supports that enol-keto photoisomerization triggers the phase transition β → γ, but does not trigger the phase transition α → β due to a larger enthalpy. The enthalpy at the phase transition β → γ is also smaller than other structural phase transitions of molecular crystals 18,21,24,30,[33][34][35] .…”
Section: Discussionmentioning
confidence: 80%
“…The difference in these transition enthalpies supports that enol-keto photoisomerization triggers the phase transition β → γ, but does not trigger the phase transition α → β due to a larger enthalpy. The enthalpy at the phase transition β → γ is also smaller than other structural phase transitions of molecular crystals 18,21,24,30,[33][34][35] .…”
Section: Discussionmentioning
confidence: 80%
“…This includes the development of Gd-hydroxypyridonate-modified MS2 nanoparticles, 14,15 Gd-1,4,7,10-tetraaza-cyclododecane-1,4,7,10-tetraacetic acid (DOTA)loaded cowpea mosaic virus (CPMV) nanoparticles, 16 as well as metal-free tobacco mosaic virus (TMV) with paramagnetic organic radical compounds. 17 Ideally, multifunctional contrast agents should be suitable for both near-infrared fluorescence (NIRF) imaging and ultrahigh field magnetic resonance imaging (UHFMRI) because these techniques work well in combination. 12,18 The imaging reagents in each case are nonionizing, and a single nanoparticle featuring such contrast agents would achieve high sensitivity, deep tissue penetration, and high spatial resolution, making them suitable for multiscale scanning from the cellular level to the organ.…”
Section: Introductionmentioning
confidence: 99%
“…17 As an approach of engineered science, researchers have studied the mechanism for the color change with temperature based on the relationship between structure and properties. 18,19 For example, Dharmarwardana et al 20 explored the thermochromic behavior of organic single crystal (SC) butoxyphenyl N-substituted naphthalene diimide (BNDI, Figure 4a) and found that the yellow monoclinic polymorph (α-phase, Figure 4b) BNDI underwent a reversible thermochromic structural transition to the triclinic polymorph (β-phase) upon heating, and subsequently changed to orange crystals after cooling down to room temperature (Figure 4c). They believed that this thermochromic behavior was based on the phase transition from a thermo-mechanical responsive SC-to-SC change (Figure 4d).…”
Section: Doi: 1030919/es8d128mentioning
confidence: 99%